THE EFFECT OF WORKLOAD AND JOB CHARACTERISTICS ON EMPLOYEE PERFORMANCE THROUGH WORK-SCHOOL CONFLICT AS MEDIATION VARIABLE - Setyowati, Ade; Nurhayati, Mafizatun (Dinasti International Journal of Digital Business Management, 2019)
This study aims to examine and analyze the effect workload and job characteristics on employee performance through work-school conflict as a mediating variable for employees who are continuing their graduate studies. The research method uses quantitative approaches. The sample selection is done by using Hair Methodl, namely by multiplying 5-15 with indicators (60 indicators), so sample obtained by 300 employees who are continuing their graduate studies in Jakarta. The technique of collecting data uses a questionnaire. Data were analyzed using SEM-PLS 3.0.The result showed that wokload had a positive and significant effect on work-school conflict, but no effect on employee performance. Job characteristics had a positive and significant effect on employee performance, but no effect on work-school conflict. Work-school conflict had negative and significant effect on employee performance. In addition, work-school conflict had full mediated work load on employee performance, but no effect mediating for characteristics to employee performance